(953) On the Maintenance of a System of Machines by One Repairman حول صيانة نظام من الآلات من قبل فنى اصلاح واحد - Ahmed Omar. (INP, 2024)
The system in question consists of n machines of the same type, where m of these machines may require the attention of a repairman at random instants. operation, the repairman spends time z repairing one of them, and the whole system can operate for time x before becoming idle. P(x): The probability that the system can operate for time x. Then, (x) = 1 - P(x) is the distribution function of the operational time of the system. It is clear that P(x) = 4% (x, 0).